Rukshah Beribadah di tengah Wabah Covid-19 dengan Mengutamakan Maslahah Mursalah - Inas Safira Salsabilla; Dea Falestri; Ika Wulandari (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2021)
Worship is the obligation of a Muslim who obeys the creator. In carrying it out is a must for his people, and there is no reason whatsoever to abandon this obligation. These obligations include Prayer, Fasting, Zakat, Hajj which are pillars or pillars of Islam that must be believed and implemented. Humans have no reason to be able to leave these obligatory prayers because in Islam there is relief or it is called Rukhsah. Rukhsah can be carried out when someone is of age which is allowed according to the terms and conditions. In this discussion, Rukhsah was carried out because there was an outbreak or a Covid-19 pandemic that had hit all over the world, including the country of Indonesia. Due to the pandemic, all activities that gather time are canceled including worship and are carried out from their respective homes. Therefore Rukhsah is densely carried out during the current pandemic to make it easier to carry out worship.